Wideband CPS-fed dipole antenna - Tan, Jinghao. (2009)
In recent years, the sudden growth in the wireless communication services has brought about a demand for bandwidth, especially in low cost consumer communication applications. Ultra wide band (UWB) dipole antenna presents a good perspective for these applications. Unlike monopole antennas, dipole antenna does not need a ground plane to radiate.